Resistance to insecticides in Myzus persicae (Sulzer) (Rhynchota Aphididae) in Italian peach orchards (Bollettino di zoologia agraria e bachicoltura, 2024)
The results obtained by biochemical assays for esterases on samples of Myzus persicae (Sulzer) are reported. Aphid populations were collected in different peach growing areas in Italy, from 1991 to 1994. Fundatrices and fundatrigenies were considered in order to evaluate the changes which occur in the level of resistance to insecticides in aphid populations in the field on the primary host. In the samples of fundatrices the heterogeneity of resistance level appears higher than in the samples collected later, which resulted almost extremely resistant.
Keywords: Myzus persicae; green peach-potato aphid; insecticide resistance; peach; Italy